Biocontrol Potential of Streptomyces hydrogenans Strain DH16 toward Alternaria brassicicola to Control Damping Off and Black Leaf Spot of Raphanus sativus - Manhas, Rajesh K.; Kaur, Talwinder (Frontiers in Plant Science, 2016)
Biocontrol agents and their bioactive metabolites provide one of the best alternatives to decrease the use of chemical pesticides. In light of this, the present investigation reports the biocontrol potential of Streptomyces hydrogenans DH16 and its metabolites towards Alternaria brassicicola, causal agent of black leaf spot and damping off of seedlings of crucifers. In vitro antibiosis of strain against pathogen revealed complete suppression of mycelial growth of pathogen, grown in potato dextrose broth supplemented with culture supernatant (20% v/v) of Streptomyces hydrogenans DH16. Microscopic examination of the fungal growth showed severe morphological abnormalities in the mycelium caused by antifungal metabolites. In vivo studies showed the efficacy of streptomycete cells and culture supernatant as seed dressings to control damping off of Raphanus sativus seedlings. Treatment of pathogen infested seeds with culture supernatant (10%) and streptomycete cells significantly improved seed germination (75-80%) and vigour index (1167-1538). Furthermore, potential of cells and culture supernatant as foliar treatment to control black leaf spot was also evaluated. Clearly visible symptoms of disease were observed in the control plants with 66.81% disease incidence and retarded growth of root system. However, disease incidence reduced to 6.78 and 1.47% in plants treated with antagonist and its metabolites, respectively. Additionally, treatment of seeds and plants with streptomycete stimulated various growth traits of plants over uninoculated control plants in the absence of pathogen challenge. These results indicate that S. hydrogenans and its culture metabolites can be developed as biofungicides as seed dressings to control seed borne pathogens, and as sprays to control black leaf spot of crucifers.